Complex Dynamics and Chaos Control of a Discrete-Time Predator-Prey Model - Rizwan Ahmed; Muhammad Rafaqat; Imran Siddique; Mohammad Asif Arefin (Discrete Dynamics in Nature and Society)
The objective of this study is to investigate the complexity of a discrete predator-prey system. The discretization is achieved using the piecewise constant argument method. The existence and stability of equilibrium points, as well as transcritical and Neimark–Sacker bifurcations, are all explored. Feedback and hybrid control methods are used to control the discrete system’s bifurcating and fluctuating behavior. To validate the theoretical conclusions, numerical simulations are performed. The findings of the study suggested that the discretization technique employed in this investigation preserves bifurcation and displays more effective dynamic consistency in comparison to the Euler method.